2018
DOI: 10.1167/iovs.18-25341
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Cerebral Microvasculopathy: Relationships and Their Genetic Contributions

Abstract: PURPOSE. Retinal microvasculopathy may reflect small vessel disease in the brain. Here we test the relationships between retinal vascular parameters and small vessel disease, the influence of cardiovascular risk factors on these relationships, and their common genetic background in a monozygotic twin cohort. METHODS. We selected 134 cognitively healthy individuals (67 monozygotic twin pairs) aged ‡60 years from the Netherlands Twin Register for the EMIF-AD PreclinAD study. We measured seven retinal vascular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
0
17
1
Order By: Relevance
“…Given the thorough characterization of our participants, we were able to correlate retinal vascular measurements with WMH on MRI, Aβ 1-42 , Tau -181 , and pTau in CSF and MMSE. Venular tortuosity was inversely correlated with WMH scores on MRI in control subjects, while in contrast an earlier study reported a positive correlation between WMH and venular tortuosity in control subjects [32] . Confirming an earlier report, we found an inverse association between macular vessel density and WMH scores in AD, possibly reflecting microvasculature changes in chronic cerebral microinfarction.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Given the thorough characterization of our participants, we were able to correlate retinal vascular measurements with WMH on MRI, Aβ 1-42 , Tau -181 , and pTau in CSF and MMSE. Venular tortuosity was inversely correlated with WMH scores on MRI in control subjects, while in contrast an earlier study reported a positive correlation between WMH and venular tortuosity in control subjects [32] . Confirming an earlier report, we found an inverse association between macular vessel density and WMH scores in AD, possibly reflecting microvasculature changes in chronic cerebral microinfarction.…”
Section: Discussioncontrasting
confidence: 78%
“…Seven retinal vascular parameters, previously shown to have good reproducibility [32] , showed no group differences between AD patients and control participants ( Fig. 2 A).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In earlier studies, we found higher intratwin pair correlations for other retinal markers such as retinal vascular parameters on fundus photography. 34 The reason for these lower correlations of OCTA markers may lie in lower reproducibility of vessel density measures, as we noticed that vessel density is very much affected by scan quality (lower quality=lower vessel density) as well as clouding of the media (floaters and cataract), making this a less reliable measure. This also explains the high number of participants who were excluded due to insufficient quality scans of both eyes (N=14).…”
Section: Clinical Sciencementioning
confidence: 94%
“…K + , PGE 2 , and EETs, for example, have been implicated in control of blood flow in both circulations (Newman, 2013;Longden et al, 2017;Gonzales et al, 2020). Recent studies have also indicated the utility of non-invasive examinations of the retinal vasculature as a marker for detecting cerebrovascular diseases, due to a similar susceptibility of both circulations to vascular risk factors such as hypertension or diabetes (Patton et al, 2005;van de Kreeke et al, 2018;McGrory et al, 2019;Querques et al, 2019). Data on gene expression in vascular cells of the retina are currently lacking, but would provide a useful standpoint for deeper comparisons of the similarities and differences between these vascular beds.…”
Section: Box 2 | a Brief Comparison Of Retinal And Brain Vasculaturesmentioning
confidence: 99%